Development and Validation of a Liquid Chromatography-Tandem Mass Spectrometry Method for Analysis of Riluzole in Human Plasma and Its Application on a Bioequivalence Study - S. Mohammadzadeh; F. Salmannejad; M. Mohammadzadeh; T. Ghari; S. Sadrai; J. Zaringhalam (Разработка и регистрация лекарственных средств, 2023)
Introduction. As the first approved drug for amyotrophic lateral sclerosis (ALS) treatment, riluzole is known as a glutamatergic neurotransmission inhibitor administrated in 50 mg tablets twice daily. For this reason, a generic product of riluzole has been developed at a lower price by Hogar-Daroo, Iran, which would benefit patients.Aim. The objective of this study is to develop and validate a novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the analysis of riluzole in human plasma samples and its application in the bioequivalence study of riluzole tablet.Materials and methods. The chromatography was performed by using a C18 column (100 mm, 4.6 mm, 5 mm), 0.1 % formic acid and acetonitrile (60 : 40, v/v) as the mobile phase, at a flow rate of 0.90 ml/min in the gradient program. Carbamazepine was used as an internal standard (IS). The method employed only 100 µL of human plasma for quantification by a liquid-liquid extraction technique. The multiple reaction monitoring modes (MRM) was used for quantification of ion transitions m/z 235.0/165.9 and m/z 137.6/110.0 for riluzole and the m/z 236.9/194.0 for the IS. Dwell time was set at 200 ms.Results and discussion. The calibration curve was linear over the concentration range 0.5–300 ng/mL. The lower limit of quantitation (LLOQ) was obtained at 0.5 ng/mL. The intra-day and inter-day accuracy ranged from 93.21 % to 101.34 % and 91.77 % to 104.88 % respectively. The intra-day and inter-day precision values ranged from 2.19 % to 5.69 % and 1.67 % to 5.31 % respectively, all within the FDA acceptable ±15 %.Conclusion. The validated method was applied in Iranian healthy subjects under fasting condition with a 50 mg riluzole tablet successfully.